Improvement of Students' Science Literacy Skills Using STEM-Based E-Modules - Prasetyo, Dwi; Marianti, Aditya; Alimah, Siti (Journal of Innovative Science Education, 2021)
Scientific literacy is one aspect of ability in facing the challenges of the 21st century. Efforts to train students 'scientific literacy skills include the use of teaching materials that can support students' scientific literacy skills in the form of STEM-based E-modules.. The purpose of this research is to analyze the effectiveness of the use of STEM-based E-modules on learning outcomes and the ability of student science literacy. This research is an experimental research design with one group pre-test and post-test design. The research sample was taken using purposive sampling method with a total of 32 students. based on research results, the average student learning outcomes obtained a value of 70.9. The results of the N-Gain analysis with the medium category show that the STEM-based E-module is effective for improving students' scientific literacy skills.. The results of the analysis with the Paired Sample T-test showed that the probability value (sig) 0.000 <0.05 means that there is a difference in the value of scientific literacy between before and after using the STEM-based E-Module. Furthermore, for each aspect of scientific literacy it also shows an increase, namely science as the body of knowledge, science as a way to investigate, science as a way to think and the interaction between science, technology and society.. Thus, it can be concluded that the development of STEM-based E-Module for environmental pollution material is effective in improving student learning outcomes and scientific literacy skills of grade VII students at the SMP / MTs level.